Active control of foams by physically based destruction mechanisms - McHardy, Christopher; Thünnesen, Julian; Horneber, Tobias; Kostova, Jordanka; Hussein, Mohamed; Delgado, Antonio; Rauh, Cornelia (Proceedings in Applied Mathematics and Mechanics, 2018)
Foams may be undesired in technical processes and need, thus, to be actively controlled. In food science engineering it is often not possible to apply chemical measures due to the required purity of the processed products. To overcome this challenge it is necessary to apply physically based foam destruction mechanisms. The present contribution deals with the prediction of foamability and the application of acoustical foam destruction from an experimental point of view. The results show that it is possible to classify the foamability of different fluids by a correlation of dimensionless numbers containing purely physico‐chemical properties (i.e. density, surface tension, viscosity). The foam stability is a consequence of the net balance of the foam generation and the foam decay. The respective time scales may be influenced by the process conditions, the fluid properties, and the selected physically based destruction mechanism. In the case of resonance excitation of foam bubbles by acoustic waves of defined frequencies selective foam destruction can be achieved. The bubbles in the foam start to oscillate and absorb energy depending on the bubble size, fluid properties, and ultrasound frequency. The resulting bubble breakdown leads to a shortening of the time scales of the foam deca

Einfluss von Hochleistungs-Ultraschall auf Getränkeschäume - Delgado, Antonio; Thünnesen, Julian; Gatternig, Bernhard (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
In der Getränkeindustrie kommt es bisweilen zur ungewünschten Schaumbildung während der Flaschenabfüllung von Säften, die zur Verringerung der Abfüllgeschwindigkeit und Dosiergenauigkeit führen. Um die Schaumbildung zu verringern, erweist sich Ultraschall als eine effektive Methode (Gallego-Juárez et al., 2015). Es wird vermutet, dass der Ultraschall Oberflächenwellen auf den Flüssigkeiten erzeugt, die Drainage im Schaum erhöht und den Schaum dadurch destabilisiert (Sandor und Stein, 1993; Morey et al., 1999). Hinzu kommen noch frequenzabhängige Eigenresonanzeffekte der Schaumblasen, wurden bereits in einer früheren Arbeit beobachtet, die sich der Optimierung von Sacklöchern in Mikrometerbereich widmete (Vaidya et al., 2016). Sie wurden aber im Hinblick auf einen forcierten Schaumzerfall bislang noch nicht betrachtet. Thema des Beitrags ist die Betrachtung des Schaumzerfalls unter dem Einfluss von Ultraschall unterschiedlicher Frequenzen. Es werden Ergebnisse von Versuchen vorgestellt, bei denen Schäume von Säften mit unterschiedlichen Ultraschallfrequenzen (35-120 kHz) zum Zerfall gebracht wurden. Neben der Erfassung der verringerten Schaumhöhe, nahm eine Hochgeschwindigkeitskamera (Fa. Shimadzu, 1 Mfps) die Lamellenvibrationen während der Beschallung auf. Es wurde ersichtlich, dass frequenzabhängig unterschiedliche Blasengrößen resonierten und kollabierten, der Tröpfchenauswurf aus den Lamellen verändert wurd
Keywords: Ultraschall; Entschäumung; Fruchtsäfte

Helical Packing Columns for Preventing Foam Formation: Experimental and Numerical Investigations - Osorio Nesme, Anuhar; Hohagen, Hans; Topic, Nikola; Thünnesen, Julian; Mobarak, Mohammad Mobarak; Lyu, Wenjing; Jahn, Alexander; Kim, Sedong; Delgado, Antonio (Chemical Engineering & Technology, 2022)
Unwanted foaming and liquid bridging inside structured packings have a negative effect on the pressure drop during thermal separation processes. A novel helical design of a packing column for preventing foaming is presented. The effective interfacial area is calculated by numerical simulations. Different designs are analyzed by varying geometrical parameters such as helix pitch, channel opening angle, and number of channels. Different F-factor values and liquid loads are evaluated. Packings with larger helix pitch exhibited lower pressure drop and reduced effective interfacial area. Smaller channel opening angles increased the pressure drop and promoted unstable flow conditions. The novel packings show lower effective interfacial area than existing structured packings, but no foaming was observed in a wide range of operating conditions.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Foaming; Mass transfer; Packing columns; Pressure drop; Structured packing

Phenomena, mechanisms and structures in wished and unwished foams in matter of biological origin - Gatternig, Bernhard; Osorio Nesme, Anuhar; Almazan Torres, Lidia; Thünnesen, Julian; Beck, Tobias; McHardy, Christopher; Bernstein, Thomas; Luzi, Giovanni; Stahl, Thomas; Rauh, Cornelia; Delgado, Antonio (Proceedings of 2019 World Congress on Advances in Nano, Bio, Robotics, and Energy ANBRE19, 2019)

Resonant Ultrasonic Defoaming in Aqueous Evaporation/Boiling Processes at Different Size Scales - Thünnesen, Julian; Gerstenberg, Christoph; Heller, Daniel; Leuner, Hannes; Einfalt, Daniel; Mchardy, Christopher; Gatternig, Bernhard; Rauh, Cornelia; Repke, Jens-Uwe; Delgado, Antonio (Chemical Engineering & Technology, 2022)
Unwanted foam bears the risk of affecting different thermal industrial processes negatively, by reduced process efficiency, contamination, and total shutdown. Mechanical defoaming methods are difficult to implement, while chemical anti-foaming agents are challenging in correct dosing. Ultrasonic defoaming actuators destroy foams purely mechanically from air-borne, but their energy consumption per area is still excessive at 10 W cm(-2). Results show that a frequency sweep between 40-168 kHz and a water-borne sonication needs power densities of around 0.1 W cm(-2) for a lab-scale experiment to a copper column still. At this power level, ultrasound enforces the foam drainage, thus reducing the foam height and the process time of the column still by 20 %. The chosen frequency range indicates a resonant behavior of small liquid-loaded lamella and plateau channels.
CRIS-Team WoS Importer:2022-06-03

Strömungsmechanische Tauglichkeitsanalyse der Fridericiana Alexandrina Navis (F.A.N.) - Thünnesen, Julian; Günther, Hans Moritz; Wawrzyn, Alexander Christopher; Dreyer, Boris; Gatternig, Bernhard (Die Fridericiana Alexandrina Navis (F.A.N.). Ein Römerboot auf dem Prüfstand – Bau und Test für Wissenschaft und Öffentlichkeit, 2022)
Keywords: Antike; Römische Kaiserzeit; Experimentelle Archäologie; Schifffahrt; Interdisziplinär; Strömungsmechanik

Ultrasonic Effects on Foam Formation of Fruit Juices during Bottling - Thünnesen, Julian; Gatternig, Bernhard; Delgado, Antonio (Eng, 2021)
Non-carbonated fruit juices often tend to foam over during bottling. The resulting foam height corresponds to the equilibrium of foam formation and decay. Therefore, the foam unexpectedly occupies more space in the bottle and carries parts of the juice out of the bottle, resulting in product loss under filled containers and hygienic problems in the plant. Chemical antifoams are likewise undesirable in most cases. Recent ultrasonic defoamers are effective but only capable outside the container and after the filling. In this article, a lateral ultrasonication through the bottle wall with frequencies between 42 and 168 kHz is used in-line for non-invasive foam prevention during filling. Foam formation during hot bottling of orange juice, apple juice, and currant nectar at 70 °C happens at flow rates between 124–148 mL/s. The comparably high frequencies have a particular influence on the fresh foams, where a large fraction of small resonant bubbles is still present. Foam volume reductions of up to 50% are reached in these experiments. A low power of 15 W was sufficient for changing the rise of entrained bubbles and minimizing the foam development from the start. The half-life of the remaining foam could be reduced by up to 45% from the reference case. The main observed effects were a changed rise of entrained bubbles and an increased drainage.
CRIS-Team Scopus Importer:2024-12-16
Keywords: foam drainage; foaming behavior; fruit juice; glass bottles; ultrasound application